From Services to Smart Services: Can Service Engineering Methods get Smarter as well? - Marx, Emanuel; Pauli, Tobias; Fielt, Erwin; Matzner, Martin (Proceedings of the 15th International Conference on Wirtschaftsinformatik (WI), 2020)
Progress in technologies such as cloud computing or artificial intelligence currently paves the way for services that rely on the exploitation of data. The resulting smart services, however, are only gradually finding their way into practical application. A reason for this delay has been identified in the limited applicability of existing service engineering methods for smart services. In this paper, we identify critical perspectives to address in smart service engineering. Subsequently, we conduct a literature review to identify the extent to which these perspectives are covered by current smart service engineering methods. Our results indicate that even though there is a significant number of smart service engineering methods, some perspectives are rarely considered. We offer practitioners and researchers an overview of the status quo of smart service engineering, thus supporting the former in the selection of methods and pointing out avenues for future research to the latte
Keywords: smart service; service innovation; smart service engineering; service development; systematic literature review